Processos conceptuais, WikiLeaks e informação - Lima, Alberto Cirilo Paz de (2012)
Metaphor was understood just as a kind of ornament used in the Poetics and Rhetoric, and not recommended for scientific discourse. From the year 1970, established itself as an extensive system of mental categorization, automatic, largely unconscious, used in everyday life and also in international relations. After the rise of Wikileaks, a site dedicated to publishing documents leaked by sources within companies or governments, created by the australian hacker Julian Assange, terms such as terrorism, cyberactivists and paranoid have been used to describe Assange, as well as terrorist organization, to WikiLeaks, which serves the purposes of those who do not want leaks to occur and more documents to be revealed, connecting his image to that of an enemy combatant, a subversive, and even a target for killing. But Wikileaks can benefit from this image, it should make it a place of ultimate challenge: anyone who has an interest in leaking classified documents knows where to turn. Within this perspective, we intend to investigate the frames that are related to Julian Assange and the WikiLeaks